Nociones Sexuales de los Estudiantes de Psicología en la Ciudad de Riohacha - Castillo Aguilar, Silbeyis; Pinto Montes, Yulieth (Universidad Antonio Nariño, 2023)
This research can be taken as a useful tool, which can provide particular conceptions about adequate sexual education, with the aim of contributing to the reduction of unwanted pregnancies, as well as to the prevention in terms of the transmission of transmitted diseases. Sexual problems and possible problems derived from these, such as maternal and child death, family dysfunction, psychological problems, not reaching the life project, among others. Thus, the general objective of this research is "To explore the notion of sexual education of psychology students at the Antonio Nariño University, Riohacha headquarters." For this reason, this research is qualitative in nature